Identification of Hub Genes in Colorectal Adenocarcinoma by Integrated Bioinformatics - Liu, Yang; Chen, Lanlan; Meng, Xiangbo; Ye, Shujun; Ma, Lianjun (Frontiers in Cell and Developmental Biology, 2022)
Improved understanding of the molecular mechanism of colorectal adenocarcinoma is necessary to predict the prognosis and develop new target gene therapy strategies. The purpose of this study is to identify hub genes associated with colorectal adenocarcinoma and further analyze their prognostic significance. In this study, the cancer genome atlas (TCGA) COAD-READ database and the gene expression profiles of GSE25070 from the Gene Expression Omnibus (GEO) were collected to explore the differentially expressed genes between colorectal adenocarcinoma and normal tissues. Utilizing the Weighted Gene Co-expression Network Analysis (WGCNA) and differential expression analysis, 82 differential co-expressed genes were identified in the collected datasets. The enrichment analysis was applied to explore the regulated signaling pathway in colorectal adenocarcinoma. In addition, ten hub genes were identified in the protein-protein interaction (PPI) network by using the CytoHubba plug-in of Cytoscape, where five genes were further proved to be significantly related to the survival rate. Compared with normal tissues, the expressions of the five genes were both downregulated in the GSE110224 dataset. Subsequently, the expression of five hub genes was confirmed by the HPA database. Finally, we used Cox regression analysis to identify genes associated with prognosis, and a 3-gene signature (CLCA1- CLCA4-GUCA2A) was constructed to predict the prognosis of patients with colorectal cancer. In conclusion, our study revealed the five hub genes and CLCA1-CLCA4-GUCA2A signature are highly correlated with the development of colorectal adenocarcinoma and can serve as promising prognosis factors to predict the overall survival rate of patients.